Trajetorias e processos formativos na/da docência: memórias e [res] significações - Marquezan, Lorena Ines Peterini (2015)
This article is anchored in the connections between personal/professional development and formative processes in/of teaching, from memories and [re]meanings. The theory postulates that the complexity in/of teaching is intertwined in the paths and formative processes of teacher, potentially inter/transdisciplinary, at different levels of education (Basic Education and Higher Education), where he/she teaches/learns, throughout life. The memories and [re]meanings of teachers allow these complex movements can be perceived in genuinely autobiographical processes. These conceptual dimensions are being elucidated and expanded in (auto) biographical research through narratives and other sources of information and iconography. The interpretative model, scenic understanding in complexity is proposed from Marinas (2007), Abrahão (2014) and Morin (2012 a, 2012 b). The autobiography of the persona, Educator Ane Carine Meurer, contains facts and arguments supporting the postulated thesis. We concluded that the persona of the (auto) biographical narrative experiences the complexity of trajectories and training processes in/of teaching, marked by the experience inter/transdisciplinary, that was being confirmed in the complex scenic understanding of the contexts of her memories and [res] meanings.